Exploring the Direction of High School Mathematics Education Based on IB DP Curriculum - Sun Hee Kim; Su Min Kim; Eun Jung Lee (Korea Society of Educational Studies in Mathematics, 2020)
International Baccalaureate (IB) is a well-known international curriculum developed by the International Baccalaureate Organization (IBO) in 1968. IB's purpose is to nurture global talent with creativity and international minds and so many countries globally such as France, Spain, and Japan have adopted the IB curriculum. This study analyzed mathematics contents and teaching and learning approaches of the IB DP which is a high school level curriculum and interviewed a mathematics teacher working for an IB DP school. As a result, the IB DP comprises a higher level of mathematics contents compared with the Korean mathematics curriculum, but guides teachers to provide conceptually-focused lessons by controlling the difficulty level of assessment items Additionally, the IB DP emphasizes inquiry-based teaching and learning approaches, use of technology, connections of mathematics and other subjects, and the consistency of teaching and learning and assessment. Based on the results, we suggest the direction of high school mathematics education in regard to mathematics contents, teaching and learning methods, and the consistency of teaching and learning methods and assessments.